PENGARUH KOMITMEN KARYAWAN, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN PEMELIHARAAN SARANA INSTALASI GARDU INDUK - Antaiwan Bowo Pranogyo; Ruland Willy Jack Sumampouw; Jahuri Jahuri (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study expects to decide and examine the impact of representative responsibility, inspiration, and workplace on worker execution at PT. PLN (Persero) UPT Pulogadung, East Jakarta.The procedure utilized in this exploration is a quantitative cooperative examination technique, and the exploration strategy utilized is a study. The populace in this study were workers of PT. PLN (Persero) UPT Pulogadung, East Jakarta. Sampling was carried out using the Slovin formula for as many as 80 people. In light of the consequences of speculation testing with a genuine level (a) 5%, a significant conclusion is obtained, either partially or simultaneously. Thus, the partial impact contribution of employee commitment to employee performance is 14.9%, the partial grant of the influence of motivation on employee performance is 0.06%, and the partial impact contribution of the work environment to employee performance is 15.8%. Meanwhile, simultaneously the assistance of the influence of employee commitment, motivation, and work environment on employee performance is 32.6%